LEADER HUMILITY, EFIKASI DIRI DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR: KONSEPTUAL REVIEW - Cahyono, Edi; Cahyono, Guntur (Cattleya Darmaya Fortuna, 2025)
This research begins with the results of previous studies that have not reached a conclusion regarding the relationship between leader humility and Organizational Citizenship Behavior (OCB). This study has two main objectives. First, to theoretically explain the relationship between leader humility and OCB. Second, this research proposes an alternative model by conceptualizing self-efficacy as a variable expected to clarify the unresolved relationship between leader humility and OCB. The study employs a systematic literature review method sourced from reputable national and international articles. The outcome of this research is a conceptual framework that is expected to provide insights into the concepts of leader humility, self-efficacy, and OCB. Leader humility can enhance OCB, and the relationship will be stronger when individuals have high self-efficacy. The propositions proposed in this study are expected to be empirically tested in future research